Application of Discussion Methods in Encouraging the Critical Thinking Ability of VIII Class Students in Fikih Lessons at MTs Madinah Bunder Susukan Cirebon - Komariyah; Muhammad Aulia Taufiqi; Fitriah (Indonesian Journal of Islamic Education and Learning, 2025)
This study was motivated by the low level of students’ critical thinking skills in the learning process, particularly in the Jurisprudence subject at MTs Madinah Bunder Susukan, Cirebon, where conventional, teacher-centered methods have resulted in passive student participation, monotonous activities, and limited problem-solving abilities. To address this issue, the research explored the application of the discussion method as a means of fostering critical thinking and active engagement among eighth-grade students, with the objectives of analyzing its implementation, identifying supporting and inhibiting factors, and examining teacher strategies in its use. Employing a qualitative approach, the study was conducted at MTs Madinah Bunder Susukan, Cirebon, using observation, interviews, and documentation for data collection, and data analysis through collection, reduction, presentation, and conclusion drawing. The results indicate that the discussion method was effectively implemented in three stages: preparation, including lesson planning, material selection from textbooks, and creating a conducive learning environment; implementation, involving group division, task assignment, collaborative discussion, presentation, and peer feedback; and closing, where unresolved questions were addressed and conclusions were drawn. Supporting factors included teacher competence and sincerity, student readiness, relevant materials, and a conducive classroom atmosphere, while inhibiting factors were non-conducive classes and absenteeism. Teacher strategies to optimize discussions involved providing engaging materials and encouraging active participation, demonstrating that the discussion method is an effective approach to enhancing critical thinking skills and classroom engagement in Jurisprudence learning.